Complete mitochondrial genome of the great sculpin Myoxocephalus polyacanthocephalus (Cottoidei: Cottidae) - Balakirev, Evgeniy S. (Mitochondrial DNA B Resour, 2019)
The complete mitochondrial genome was sequenced in two specimens of the great sculpin Myoxocephalus polyacanthocephalus by high-throughput sequencing technology (Ion S5 platform). The genome sequences are 16,651 and 16,652 bp in size, and the gene arrangement, composition, and size are similar to the other sculpin mitochondrial genomes published previously. Overall base composition of the complete mitochondrial DNA is A (26.9%), G (17.0%), C (29.5%), and T (26.6.0%), the percentage of A and T (53.5%) is higher than G and C (46.5%). The difference between the two genomes studied is low, 0.15%. A relatively low level of divergence (3.48%) is detected between M. polyacanthocephalus and M. scorpius, which however is high enough to consider them as separate biological species.